The Use of Compound Words in the Guardian News Website - Artawan, I Gede Widia; Nugraha Putra, I Gusti Bagus Wahyu; Arcana Putra, I Wayan Heka (Faculty of Humanities, Universitas Jenderal Soedirman, 2023)
This study aims to find out the types of compound words and formation of compound words found in the Guardian News Websites. The data were classified and analyzed by applying the theory from Delahunty & Garvey (2010) and supported by the theory from McCarthy (2002), about the types and the formation of compound words. This study applied descriptive qualitative research and the data were collected using observation and documentation technique. The results of this study found that there were 164 compound words in fourteen selected news articles on the Guardian News Website. The first result showed that there are four types of compound words found in this study: 101 (62%) compound nouns, 33 (20%) compound verbs, 25 (15%) compound adjectives, and 5 (3%) prepositions compound. The second result showed that there are four types of compound word formation: 103 (63%) closed compound, 29 (18%) open compound, 22 (13%) hyphenated compound, and 10 (6%) mixed compound.